Increased MMP-2 in healthy postmenopausal women - Muzzio, Maria Luz (2011)
Background: Matrix metalloproteases 2 (MMP-2) and 9 (MMP-9) are involved in the atherosclerosis process. The objective of the study was to evaluate MMP-2 and MMP-9 activities and other circulating inflammatory factors in healthy postmenopausal women (PMW) as a model of subclinical atherosclerosis. Methods: Twenty-three PMW and 13 premenopausal women (PreMW) were selected following established criteria. The main measurements in plasma samples were: lipid –lipoprotein profile, high-sensitivity C-reactive protein (hs-CRP) (immunoturbidimetry), soluble vascular cellular adhesion molecules (sVCAM-1) enzyme-linked immunosorbent assay and MMP activity by zymography. Results: The relative areas of MMP-2 were increased in PMW: 1.1 (0.1) versus 0.6 (0.05), P , 0.02. MMP-9 was only detected in three PMWand one PreMW. MMP-2 correlated with HDL-cholesterol (r ¼ 20.51), triglycerides (r ¼ 0.67), apolipoprotein B (r ¼ 0.47), hs-CRP (r ¼ 0.42), homeostasis model assessment (r ¼ 0.53) and waist circumference (r ¼ 0.40), at least P , 0.02. sVCAM-1 showed no difference between groups: 28.7 (5.5) versus 35.5 (20) ng/mL, but correlated with MMP-2 and hs-CRP (r ¼ 0.46 and r ¼ 0.48 respectively, P , 0.05). Conclusions: In postmenopause, the increase in MMP-2 reflects the systemic specific inflammatory process that accompanies atherogenesis.